Ethno-microbiology e-catalog of traditional malay and dayak cuisine in sintang - Hanum Mukti Rahayu; Hayadi, Arif Ergi; Anandita Eka Setiadi (JURNAL BIOEDUKATIKA, 2025)
Sintang, located in West Kalimantan, is known for its diverse ethnic groups and traditional dishes that are influenced by ethnomicrobiology. This research aims to evaluate the practicality and student reactions to an e-catalog focused on the ethnomicrobiology of Malay and Dayak cuisine from Sintang. The study employs a development approach (R&D) using the 4-D model, which includes four phases: define, design, develop, and disseminate. Data analysis involves assessing the validity and student feedback on the e-catalog. During the define phase, 7 traditional cuisine—pekasam babi, pekasam ikan, rusip, tapai ubi, tempoyak, and tuak ketan—were identified. These dishes were organized into an electronic catalog format in the design phase. The e-catalog was then tested for effectiveness in the development phase, receiving high validity ratings in material (91%), media (96%), and language (89%) aspects. Student responses were very positive, with large-scale test results at 83.80% and small-scale test results at 86.08%. The development of this instructional material was guided by the principles of contextual and culturally responsive education. The findings indicate that the ethnomicrobiology-based e-catalog is a viable and effective learning resource for biotechnology topics. By embedding elements of local wisdom, particularly those relevant to the Sintang region, the e-catalog promotes meaningful learning experiences that are closely aligned with students’ real-life contexts and cultural backgrounds.